Analisis Dan Perancangan Sistem Informasi E-Learning Berbasis Learning Management System (LMS) Moodle Di SMA Negeri 1 Sukawati - Ni Luh Aristya Dewi; A.A. Istri Ita Paramitha; Eka Grana Aristyana Dewi (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2022)
The impact of the spread of the COVID-19 virus on educational institutions is changing the education system into online learning. One of the formal educational institutions affected by this change is SMA Negeri 1 Sukawati. This school previously developed a Moodle-based learning information system in early 2020 with the aim of helping the online learning process. Starting from UTBK activities that require a system to accommodate student scores and the need for online learning activities. However, based on the results of unstructured interviews obtained from the admin, teachers, and students, that there are still many shortcomings in Moodle E-Learning. The lack of a system that has been mentioned will have an impact on the performance of the Moodle system in supporting online learning activities. The method used is the SDLC research method with a prototype development model. The results of the study used the PSSUQ questionnaire which consisted of 4 categories, namely the SYSUSE category (usability) of 3.27, INFOQUAL (information) of 3.37, the INTQUAL category (display) of 3.40, and the OVERALL category of 3.18. The results of the PSSUQ score where the INTQUAL category gets the lowest score or close to a scale of 7 or is interpreted as less good so an interview is needed with the result that the Moodle Information System in terms of appearance is acceptable, but not yet attractive to users as a whole, then in terms of functionality, the Moodle Information System has several functions that have not run properly and tested using the Black Box method, and resulted in an average overall score of 100, which means that the overall function is very good.